2020
DOI: 10.3390/su12166653
|View full text |Cite
|
Sign up to set email alerts
|

Making STEM Education Objectives Sustainable through a Tutoring Program

Abstract: The objective of this research was two-fold. First, to determine the impact of a Science, Technology, Engineering and Mathematics (STEM) Education program on school performance amongst primary education students. Second, to identify the potential benefits of this program on the key competences of university students in Primary Education Teacher Training. The primary education students’ sub-sample, after being matched on key covariates, was randomly assigned either to the experimental (N = 25) or control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Many of these activities are carried out by universities and schools having to work together. Cooperation between universities and schools can be good for both pre-service teachers and students at the school (Fernández-Martín et al, 2020). This is also in line with what Murphy (2022) found, suggesting that one of the benefits of STEM education is that people in the STEM community work together more.…”
Section: Implementation Of Stem-tpd Outside Of Lecturessupporting
confidence: 80%
See 1 more Smart Citation
“…Many of these activities are carried out by universities and schools having to work together. Cooperation between universities and schools can be good for both pre-service teachers and students at the school (Fernández-Martín et al, 2020). This is also in line with what Murphy (2022) found, suggesting that one of the benefits of STEM education is that people in the STEM community work together more.…”
Section: Implementation Of Stem-tpd Outside Of Lecturessupporting
confidence: 80%
“…Outside of the university curriculum, a number of professional development activities were also carried out (n=12 or 17 percent). The programme is implemented in two ways: either in collaboration with schools (e.g., Fernández-Martín et al, 2020;Küçük Demir, 2021) or on its own without partnering with schools (e.g., Dubek & Doyle-Jones, 2021;Estapa & Tank, 2017).…”
Section: Position Of Stem-tpd In Pre-service Teacher Educationmentioning
confidence: 99%
“…Besides identifying the impact of STEM (Science, Technology, Engineering, and Mathematics) education programs on the academic performance of elementary students, Fernández-Martín et al (2020) observed the key focus of sustainability on the employability of college students through mentoring programs. They used the course materials provided by the Nurture Thru Nature (NtN) program to evaluate the impact of STEM courses on Spanish elementary students and the effect of mentoring programs on the employability of college students [3]. Studies in Vietnam have shown that STEM education could motivate students and enhance their attitude towards learning [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results obtained appear to confirm the possible effects of improvement that participation in this type of program entails for the variables of learning strategies and social skills. Therefore, by using other statistics, we are avoiding a frequent error in educational research studies considered as a "Type II error" that affects the validity of statistical conclusions, and that consists of not detecting the effect of the intervention when it really exists [72], as has been done in other studies [65,66,73,74].…”
Section: Discussionmentioning
confidence: 99%